DETERMINAN KEPATUHAN WAJIB PAJAK PEGAWAI NEGERI SIPIL (PNS) DI KECAMATAN SUGIO LAMONGAN - Siti Shoimah; Martha Laila Arisandra; Moh. Ali Wafa (BBM (Buletin Bisnis & Manajemen), 2023)
This research aims to determine the Taxpayer Compliance (religiosity, tax sanctions, tax knowledge, fiscal services and tax amnesty. This research was analytical research with a quantitative approach. The    population of this research is the taxpayer of Persons who work as civil servants in Sugio district of Lamongan district. Sampling technique using sampling quota which amounted to 32 respondents, with data collection techniques using questionnaires. The collected data was analyzed using SPSS program version 25 with multiple linear regression analysis. The results of this study indicate that: (1) there is no effect of tax levy sanction on taxpayer compliance indicated by the value of t value of 0.269 and significance value 0.769, (2) there is no influence of tax knowledge variable on taxpayer compliance indicated by t value of 1.054 and significance value of 0.299, (3) there is the effect of tax service variable on taxpayer compliance indicated by the value of t count of 4.205 and the significance value of 0.000, (4) there is no effect of tax amnesty variable on taxpayer compliance is indicated with t value equal to -0.553 and a significance value of 0.584.Keywords: tax sanctions, religiosity, fiscal service, tax amnesty and taxpayer compliance